Moralitas Sosial dan Peran Aparat Penegak Hukum dalam Politik Hukum Pidana pada Kasus Kekerasan Seksual di Kabupaten Cianjur - Sintia Mona Pratama; Neng Anisa Fitri Nurdiani; Salha Aulia; Muhammad Reyhanz Nugraha; Rahmat Al Kaffi; Susan Srinovi; Siti Alia Zahra; Muhammad Fadly; Kori Hermawanti (Majelis: Jurnal Hukum Indonesia, 2026)
This study is a case study that analyzes the handling of sexual violence in Cianjur Regency, examining the relationship between social morality, the role of law enforcement officials, and the effectiveness of criminal law policy after the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law). This study uses a descriptive qualitative approach with an empirical juridical method through a sociological approach to law. Data was obtained through interviews with law enforcement officials, field observations, and a literature review of relevant legislation and scientific literature. The results of the study show that the handling of sexual violence cases in Cianjur Regency still faces obstacles in the form of weak social morality, strong stigma against victims, and a patriarchal culture that affects reporting and law enforcement processes. In addition, the role of law enforcement officials has not been optimal due to limited capacity, coordination between institutions, and a lack of sensitivity to the victims' perspective. This study recommends strengthening the capacity of law enforcement officials through training on gender perspectives and the implementation of the TPKS Law, continuous education on social morality at the community level, and strengthening inter-agency coordination to improve victim protection and the effectiveness of criminal law policy in Cianjur Regency.